Christian nationalism: Letter to the US church - Martell, Loida I. (Review and expositor, 2024)
The epistles in the Second Testament were addressed to specific churches and offered instruction, encouragement, and counsel on dealing with contextually specific issues the churches faced in the first century. In that spirit, this “Letter to the US church” identifies white Christian nationalism and the dangers that this distorted, unbiblical, and poorly theologically constructed notion of Christianity portend to our country, especially the most vulnerable among us. The letter also provides both theological resources as well as encouragement for those desiring to speak prophetically against injustice and stand with those who suffer and cry out for hope and life.